Glutamine Accelerates Post-Exercise Recovery of Arms Power, Leg Power, and Smash Velocity at 48 Hours for Non-Elite Badminton Athletes - Himawan Wismanadi; Joesoef Roepajadi; Pudjijuniarto Pudjijuniarto; Afif Rusdiawan; Cleonara Yanuar Dini; Anindya Mar’atus Sholikhah (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Badminton is a sport that is characterized by long-lasting muscle contractions in continuous smash movements which lead to fatigue and glutamine can potentially reduce the incidence of muscle fatigue. The aim of the study is to investigate glutamine affecting post-exercise recovery in non-elite badminton athletes. It was a randomized group pre-test and post-test design. Twenty male students were involved and divided into 2 groups: The placebo (Plac) group was only given instruction for jumping smash activities and mineral water, while the glutamine (Glut) group was jumping smash activities and mineral water containing glutamine. The jumping smash activities were carried out in 10 sets with 20 repetitions with a rest period of 30 seconds per set. Glutamine was given 3 times after 1 hour of jumping smash activities, 24 hours, and 48 hours with a dose of 0.4 grams/KgBW. There were significant differences in the vertical jump, leg power, arm power, and smash velocity in pre-post-2 between the Placebo and Glutamine groups with p<0.05. Meanwhile, no difference was observed in the vertical jump, leg power, arm power, and smash velocity (p>0.05) between the Placebo and Glutamine groups 72 hours after the jumping smash activities (post 3). The administration of glutamine at a dose of 0.4 gram/Kg BW given three times post-jumping smash (eccentric) exercise can accelerate the 48-hour post-exercise recovery of vertical jump, arm power, leg power, and smash velocity. Badminton athletes who play matches daily are expected to consume glutamine to speed up recovery.